Surgery for Bentall endocarditis: short- and midterm outcomes from a multicentre registry. (17th May 2020) - Sponga, Sandro; Di Mauro, Michele; Malvindi, Pietro G; Paparella, Domenico; Murana, Giacomo; Pacini, Davide; Weltert, Luca; De Paulis, Ruggero; Cappabianca, Giangiuseppe; Beghi, Cesare; De Vincentiis, Carlo; Parolari, Alessandro; et al.
Abstract: OBJECTIVES: Endocarditis after the Bentall procedure is a severe disease often complicated by a pseudoaneurysm or mediastinitis. Reoperation is challenging but conservative therapy is not effective. The aim of this study was to assess short- and midterm outcomes of patients reoperated on for Bentall-related endocarditis. METHODS: Seventy-three patients with Bentall procedure-related endocarditis were recorded in the Italian registry. The mean age was 57 ± 14 years and 92% were men; preoperative comorbidities included hypertension (45%), diabetes (12%) and renal failure (11%). The logistic EuroSCORE was 25%; the EuroSCORE II was 8%. RESULTS: Preoperatively, 12% of the patients were in septic shock; left ventricular-aortic discontinuity was present in 63% and mitral valve involvement occurred in 12%. The most common pathogens were Staphylococcus aureus (22%) and Streptococci (14%). Reoperations after a median interval of 30 months (1–221 months) included a repeat Bentall with a bioconduit (41%), a composite mechanical (33%) or biological valved conduit (19%) and a homograft (6%). In 1 patient, a heart transplant was required (1%); in 12%, a mitral valve procedure was needed. The hospital mortality rate was 15%. The postoperative course was complicated by renal failure (19%), major bleeding (14%), pulmonary failure (14%), sepsis (11%) and multiorgan failure (8%). At multivariate analysis, urgent surgery was a risk factor for early death [hazard ratio 20.5 (1.9–219)]. Survival at 5 and 8 years was 75 ± 6% and 71 ± 7%, with 3 cases of endocarditis relapse. CONCLUSIONS: Surgery is effective in treating endocarditis following the Bentall procedure although it is associated with high perioperative mortality and morbidity rates. Endocarditis relapse seems to be uncommon.